2015
DOI: 10.12968/ijtr.2015.22.1.36
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of auditory stimulation in children with autism spectrum disorders: A case–control study

Abstract: Background/Aim: The Listening Program (TLP) is a sound-based intervention that claims to treat the behavioural challenges of children diagnosed on the autism spectrum with sensory processing difficulties. There is a paucity of peer-reviewed evidence supporting its use. The purpose of this study was to determine whether TLP reduces sensory over-responsitivity (SOR) to auditory stimuli. Methods: Data were collected over a 28-week period using an ABAB multiple events case-control design of testing and treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Each child experienced two, 15-minute listening sessions for 10 weeks between two five week, non-intervention observation periods (Gee, et al, 2014). The results demonstrated that there was a change in all three case studies (Gee, et al, 2014). Measures included the SenSOR scales, the auditory defensiveness scale in the Sensory Processing Measure, and the overall total score from the Sensory Processing Measure.…”
Section: The Listening Programmentioning
confidence: 99%
See 3 more Smart Citations
“…Each child experienced two, 15-minute listening sessions for 10 weeks between two five week, non-intervention observation periods (Gee, et al, 2014). The results demonstrated that there was a change in all three case studies (Gee, et al, 2014). Measures included the SenSOR scales, the auditory defensiveness scale in the Sensory Processing Measure, and the overall total score from the Sensory Processing Measure.…”
Section: The Listening Programmentioning
confidence: 99%
“…Applications of TLP are applicable within a diverse array of settings including therapy clinics, schools, hospitals, homes, assisted living facilities, and military bases (Doman, 2015). Gee, et al (2014) conducted a case control with three children ages 5-10 diagnosed with ASD in order to observe the changes in sensory processing after TLP intervention. Each child experienced two, 15-minute listening sessions for 10 weeks between two five week, non-intervention observation periods (Gee, et al, 2014).…”
Section: The Listening Programmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, researchers noted that the use of a Therapeutic Listening® program helped prepare children for purposeful activities within their sensory diets (Hall & Case-Smith, 2007). Gee, Thompson, Pierce, Toupin, and Holst (2015) conducted a case-control study to determine the effective of the The Listening Program (TLP) on children ages 5-10, diagnosed with ASD and sensory processing difficulties who were experiencing behavioral challenges. After the 28-week study, the majority of participants showed an overall decrease in behavioral challenges.…”
Section: Sensory Based Interventionsmentioning
confidence: 99%